Knowledge Level of Beneficiaries Farmers as Compared to Non-Beneficiaries Farmers Regarding Turmeric Cultivation - , Yuvaraj Singh Dhruw; , V. K. Painkra; , S. K. Pradhan (Archives of Current Research International, 2024)
The present study was conducted to know the knowledge level of beneficiaries farmers as compared to non-beneficiaries farmers about turmeric cultivation. The present study was conducted during the year 2015-16 and 2016-17 in Chhattisgarh plains. A sample size of 160 beneficiaries respondents, proportionate random methods were used and equal numbers of non-beneficiaries respondents were also selected randomly from the same villages. In this way, a total of 320 farmers were considered as respondents to respond as per the interview schedule design for the study. The study revealed that the majority of the beneficiaries (73.12%) and non-beneficiaries (75.62%) had a medium level of knowledge, followed by 19.38 percent of the beneficiaries and 20.63 percent of the non-beneficiaries had a low level of knowledge and 7.50 percent of the beneficiaries and 3.75 percent of the non-beneficiaries had a high knowledge about turmeric cultivation. The high level trend of knowledge of the respondents in beneficiaries need to be maintained in the same manner, whereas it would be desirable to develop knowledge of non-beneficiaries respondents to high level by involving them in extension programme i.e. training and demonstration etc.